Differential Modulation of miR-122 Transcription by TGFβ1/BMP6: Implications for Nonresolving Inflammation and Hepatocarcinogenesis - Martha Paluschinski; Claus Kordes; Mihael Vucur; Veronika Buettner; Christoph Roderburg; Haifeng C. Xu; Prashant V. Shinte; Philipp A. Lang; Tom Luedde; Mirco Castoldi (Cells, 2023)
Chronic inflammation is widely recognized as a significant factor that promotes and worsens the development of malignancies, including hepatocellular carcinoma. This study aimed to explore the potential role of microRNAs in inflammation-associated nonresolving hepatocarcinogenesis. By conducting a comprehensive analysis of altered microRNAs in animal models with liver cancer of various etiologies, we identified miR-122 as the most significantly downregulated microRNA in the liver of animals with inflammation-associated liver cancer. Although previous research has indicated the importance of miR-122 in maintaining hepatocyte function, its specific role as either the trigger or the consequence of underlying diseases remains unclear. Through extensive analysis of animals and in vitro models, we have successfully demonstrated that miR-122 transcription is differentially regulated by the immunoregulatory cytokines, by the transforming growth factor-beta 1 (TGFβ1), and the bone morphogenetic protein-6 (BMP6). Furthermore, we presented convincing evidence directly linking reduced miR-122 transcription to inflammation and in chronic liver diseases. The results of this study strongly suggest that prolonged activation of pro-inflammatory signaling pathways, leading to disruption of cytokine-mediated regulation of miR-122, may significantly contribute to the onset and exacerbation of chronic liver disease.